THE EFFECT OF TEAM LEADERS ON MOTIVATION AND PERFORMANCE OF EMPLOYEES - Durmaz, DYakup; DUSUN, ZeynepDerya; DEMIR, Beyhan (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
These days, due to the technological developments and increasing competition, business managers have an important role in reaching the business goals. In order to reach the goals, managers should have leadership qualities and value motivation and performance of employees. The purpose of this study is to determine the effects of leadership qualities of managers on motivation and performance of employees considering basic leadership qualities. Employees motivation increase depending on the leadership qualities managers have. It has been confirmed that there is a strong and directly proportional relationship between leadership or managers and performances of employees. The aim of this study is to understand how leadership qualities affect the motivation of employees.